Effects of an individualized vs. standardized Vitamin D supplementation on the 25(OH)D level in athletes - Tuma, C.; Schick, A.; Pommerening, N.; Braun, H.; Thevis, M. (Nutrients, 2023)
Vitamin D is crucial to the health and performance of athletes. Although the exact vitamin D requirements for athletes have not been established, maintaining a 25(OH)D level of at least 40 ng/mL is considered beneficial. This randomized controlled intervention study aimed to determine whether an individual loading dose formula for vitamin D supplementation is more effective than standardized supplementation and suitable enough for athletes to meet a target value of 40 ng/mL. In a 10-week supplementation study conducted during the winter months in Germany, 90 athletes with insufficient vitamin D levels (25(OH)D < 30 ng/mL) were randomly assigned to receive either a universal dose of 2000 IU/day of vitamin D or a loading dose of 4000 IU/day, followed by a maintenance dose of 1000 IU/day. The total 25(OH)D concentration was measured from dried blood spots at three time points: at baseline, at the computed date of 40 ng/mL, and after the 10-week period. Additionally, a vitamin-D-specific questionnaire was issued. On the day when 25(OH)D blood concentrations of 40 ng/mL were calculated to prevail, the individualized group had a significantly higher 25(OH)D level than the standardized group (41.1 ± 10.9 ng/mL vs. 32.5 ± 6.4 ng/mL, p < 0.001). This study demonstrated that the examined formula is suitable enough for athletes to achieve a 25(OH)D concentration of 40 ng/mL. This indicates that a personalized approach is more effective than a one-size-fits-all approach in restoring adequate vitamin D levels in athletes.